Brecha de género en el sistema público pensional colombiano al año 2023. Un análisis descriptivo de las cifras de colpensiones de pensionados por vejez. (2024)
Within the framework of the Colombian Pension System, a gender gap has been identified in old-age pensions. Through descriptive statistics and hypothesis tests, it was confirmed that there is not enough statistical evidence to affirm that men retire more than women in the public old-age pension fund in the year 2023. This research was approached from different angles, including them, a) the dynamics of operation of the Colombian Pension System, b) its history and most important laws, c) the representativeness of the Pension Funds throughout the Pension System and clearly, d) the gender variable in the data obtained. With the official data collected, Table 5 was created, to which a descriptive analysis of the data by gender was carried out, to subsequently obtain the proportion of pensioners compared to the entire Colombian population of pension age in 2023.